(untitled) (Research, Society and Development, 2025)
Introduction: Polypharmacy, defined as the concomitant use of multiple medications, is common among older adults due to the presence of multiple comorbidities. Objective: To analyze the relationship between polypharmacy and mental health in older adults, focusing on the development or worsening of disorders such as depression and cognitive decline. Methodology: A systematic review was conducted in the CAPES, BVS, and SciELO databases, considering articles published between 2019 and 2024 in English, Portuguese, or Spanish, with open access and full-text availability. Studies including elderly individuals (≥ 60 years) addressing the influence of polypharmacy on mental health were selected. Exclusion criteria encompassed articles that did not directly address this relationship, were inaccessible, or were published before 2019. Results: Of the 12 studies analyzed, 10 indicated a negative correlation between polypharmacy and mental health, highlighting increased depressive symptoms. However, some studies suggested potential benefits, such as protection against cognitive decline when polypharmacy is adequately managed. Conclusion: Inadequate polypharmacy management can exacerbate mental disorders and impair the quality of life of older adults. Further research is needed to explore its impacts, considering both risks and potential benefits.